An Epigraphical Journey through Bengal - Siddiq, Mohammad Yusuf (Islamic Studies, 2021)
The study of the architectural inscriptions of the Bengal Sultanate provides us with a new opportunity to look into the rich cultural history of this hinterland of South Asia. Most of the early Islamic monuments in the region had calligraphic works on them, as inscriptions were considered a powerful medium to convey visual, cultural, and spiritual messages to people. These inscriptions were rendered in various styles such as Kūfī, Thuluth, Naskh, Riqa‘, Rayḥānī, Muḥaqqaq, Ṭughrā’, and Bihārī. This article focuses on some interesting inscriptions discovered in various parts of Bengal. Special attention is given to the analysis of information derived from them in their historical contexts, such as the names of the contemporary rulers, local administrative officers, religious figures, military commanders, and their titles. These findings help us understand the contemporary political, administrative, social, religious, and cultural aspects of the region.